PENGARUH PENAMBAHAN DOSIS RAFINOSA DALAM PENGENCER SUSU SKIM TERHADAP MOTILITAS, PERSENTASE HIDUP DAN ABNORMALITAS SPERMATOZOA SAPI ONGOLE - Munzir, Indah Iftinandari; Suharyati, Sri; Hartono, Madi (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
Studies conducted in the Technical Services Unit Regional Center for Artificial Insemination Regions (UPTD-BIBD) Lampung, RegencyTerbanggiBesar, Central LampungRegency, Lampung Province in May 2016 aims to determine the effect of dose rafinosa in dilution of skim milk on motility, abnormality and the percentage of spermatozoa Ongole cattle alive. The experimental design used was completely randomized design with 6 treatments of 0.5%; 1.0%; 1.5%; 2.0%; 2.5%; 3.0% in diluent and skim milk respectively -masing treatment be repeated 4 times. The data obtained were analyzed using analysis of varian at significance level of 5% or 1%, and for variable real test of orthogonal polynomials on the real level of 5% or 1% to determine the optimum dose rafinosa. The results showed that increasing doses rafinosa give effect not significantly different (P> 0.05) on percentage motility after equilibration and prefreezing, the percentage of live sperm after equilibration and prefreezing, as well as the percentage of spermatozoa abnormalities after prefreezing, and PTM, but give effect highly significant (P <0.01) on the percentage of sperm motility PTM, the percentage of live sperm PTM, and the percentage of abnormal spermatozoa after equilibration. Extra doses of raffinose based test pattern orthogonal polynomial regression on percentage motility PTM equation Ó¯ = 25.08 + 4x , the percentage of live sperm PTM equation Ó¯ = 22.55 + 5,77x , and the percentage of abnormal spermatozoa after equilibration with the equation Ó¯ = 6,36-1,71x .Â Keywords: Rafinose, Skim Milk, Motility, Percentage of Live, Abnormalities Spermatozoa,Ongole Cattle